Beyond the case the logics and practices of comparative ethnography (Global and comparative ethnography, 2020)
"The social sciences have seen a substantial increase in comparative and multi-sited ethnographic projects over the last three decades. Yet, at present, researchers seeking to design comparative field projects have few scholarly works detailing how comparison is conducted in divergent ethnographic approaches. In Beyond the Case, Corey M. Abramson and Neil Gong have gathered together several experts in field research to address these issues by showing how practitioners employing contemporary iterations of ethnographic traditions such as phenomenology, grounded theory, positivism, and interpretivism, use comparison in their works. The contributors connect the long history of comparative (and anti-comparative) ethnographic approaches to their contemporary uses. By honing in on how ethnographers render sites, groups, or cases analytically commensurable and comparable, Beyond the Case offers a new lens for examining the assumptions, payoffs, and potential drawbacks of different forms of comparative ethnography." |c --From publisher's description.